Insitusi Internasional sebagai Representasi Individu: Faktor Ketidakefektifan ASEAN Institute for Peace and Reconciliation dalam Mekanisme Penyelesaian Konflik di Asia Tenggara - Irfansyah, Fadhila; Rosyidin, Mohamad (Journal of International Relations, 2019)
The Association of Southeast Asia Nations (ASEAN) has several mechanisms for resolving conflicts, the ASEAN Institute for Peace and Reconciliation (AIPR) is one of them, which formed by the legitimacy of ASEAN to resolve conflicts. But, since it was formed, A-IPR did not going well resolving those conflicts. Southeast Asian countries prefer to resolve conflicts in their own ways, namely by means of unilateralism and bilateralism. So A-IPR becomes a pseudo institutionbecause it doesn't work according to the function they’ve been set. Some conflicts, such as theborder conflicts between Thailand and Cambodia, Myanmar's internal conflict, and the Sabahconflict between Malaysia and the Philippines also went that way. These countries prefer toresolve those conflicts in their own way rather than through the AIPR path. Even though AIPR has a management and conflict resolution function. This research wants to explain the reasons of the Southeast Asian countries not using A-IPR as conflict resolution mechanism using the perspective of idiosyncratism. This study argues that the ineffectiveness of A-IPR is because the institution was formed based solely on the personal preferences of the initiatior which is Susilo Bambang Yudhoyono without considering the desires of other countries. So that A-IPR only becomes a pseudo institution without support from it’s member.